Scalable spin squeezing for quantum-enhanced magnetometry with Bose-Einstein condensates - Müssel, Wolfgang; Strobel, Helmut; Linnemann, Daniel; Hume, David B.; Oberthaler, Markus K. (Physical review letters, 2014)
A major challenge in quantum metrology is the generation of entangled states with a macroscopic atom number. Here, we demonstrate experimentally that atomic squeezing generated via nonlinear dynamics in Bose-Einstein condensates, combined with suitable trap geometries, allows scaling to large ensemble sizes. We achieve a suppression of fluctuations by 5.3(5) dB for 12 300 particles, from which we infer that similar squeezing can be obtained for more than 107 atoms. With this resource, we demonstrate quantum-enhanced magnetometry by swapping the squeezed state to magnetically sensitive hyperfine levels that have negligible nonlinearity. We find a quantum-enhanced single-shot sensitivity of 310(47) pT for static magnetic fields in a probe volume as small as 90 μm3.